Response of human chondrocytes and mesenchymal stromal cells to a decellularized human dermis - Giavaresi Gianluca; Bondioli Elena; Melandri Davide; Giardino Roberto; Tschon Matilde; Torricelli Paola; Cenacchi Giovanna; Rotini Roberto; Castagna Alessandro; Veronesi Francesca; Pagani Stefania; Fini Milena (BMC Musculoskeletal Disorders, 2013)
Abstract Background Although progress has been made in the treatment of articular cartilage lesions, they are still a major challenge because current techniques do not provide satisfactory long-term outcomes. Tissue engineering and the use of functional biomaterials might be an alternative regenerative strategy and fulfill clinical needs. Decellularized extracellular matrices have generated interest as functional biologic scaffolds, but there are few studies on cartilage regeneration. The aim of this study was to evaluate in vitro the biological influence of a newly developed decellularized human dermal extracellular matrix on two human primary cultures. Methods Normal human articular chondrocytes (NHAC-kn) and human mesenchymal stromal cells (hMSC) from healthy donors were seeded in polystyrene wells as controls (CTR), and on decellularized human dermis batches (HDM_derm) for 7 and 14 days. Cellular proliferation and differentiation, and anabolic and catabolic synthetic activity were quantified at each experimental time. Histology and scanning electron microscopy were used to evaluate morphology and ultrastructure. Results Both cell cultures had a similar proliferation rate that increased significantly (p < 0.0005) at 14 days. In comparison with CTR, at 14 days NHAC-kn enhanced procollagen type II (CPII, p < 0.05) and aggrecan synthesis (p < 0.0005), whereas hMSC significantly enhanced aggrecan synthesis (p < 0.0005) and transforming growth factor-beta1 release (TGF-β1, p < 0.0005) at both experimental times. Neither inflammatory stimulus nor catabolic activity induction was observed. By comparing data of the two primary cells, NHAC-kn synthesized significantly more CPII than did hMSC at both experimental times (p < 0.005), whereas hMSC synthesized more aggrecan at 7 days (p < 0.005) and TGF-β1 at both experimental times than did NHAC-kn (p < 0.005). Conclusions The results obtained showed that in in vitro conditions HDM_derm behaves as a suitable scaffold for the growth of both well-differentiated chondrocytes and undifferentiated mesenchymal cells, thus ensuring a biocompatible and bioactive substrate. Further studies are mandatory to test the use of HDM_derm with tissue engineering to assess its therapeutic and functional effectiveness in cartilage regeneration.